Breast Cancer Local Recurrence Risk in Implant-Based Breast Reconstruction with Macrotexturized and Microtexturized Prosthesis: A Multicentric Retrospective Cohort Study - Valeriano Vinci; Francesco Klinger; Riccardo Di Giuli; Andrea Vittorio Emanuele Lisa; Barbara Catania; Stefano Vaccari; Edoardo Caimi; Emanuele Pitassi; Jacopo Di Filippo; Damiano Gentile; Corrado Tinterri; Gerardus Johannes Janszen; et al. (Indian Journal of Plastic Surgery)
Background Nowadays, implant-based breast reconstruction is a common technique after mastectomy. The widespread use of implant employment is prompting significant concerns regarding the oncological safety of prostheses and the potential impact of surface texture on the recurrence of local breast cancer. This article examines the oncological outcomes associated with postmastectomy breast reconstructions using micro- and macrotexturized implants, focusing on the incidence and relative risk (RR).